2020
DOI: 10.1192/j.eurpsy.2020.108
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical correlates of self-harm and suicidality during admission of children in a mental health inpatient unit

Abstract: Background Self-harm and suicidality are common presentations in children and adolescents requiring a mental health inpatient admission. Although there are several studies on adolescents, there is relatively limited research into childhood self-harm and suicidality during such admissions. Methods A retrospective electronic file review was conducted on all children discharged from a national mental health inpatient children’s unit over a 6-year period. Several independent variables were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
(123 reference statements)
1
4
0
Order By: Relevance
“…The first theme related to how and when staff should intervene when incidents of self‐harm occur. Participants' accounts suggest that self‐harm by CYP is a common occurrence in mental health inpatient settings, which is consistent with existing research (Kipoulas et al, 2021; Monto et al, 2018). Also consistent with research in this area is the finding that parents and staff find incidents of self‐harm by CYP distressing (Ferrey et al, 2016; Ribeiro Coimbra & Noakes, 2021).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The first theme related to how and when staff should intervene when incidents of self‐harm occur. Participants' accounts suggest that self‐harm by CYP is a common occurrence in mental health inpatient settings, which is consistent with existing research (Kipoulas et al, 2021; Monto et al, 2018). Also consistent with research in this area is the finding that parents and staff find incidents of self‐harm by CYP distressing (Ferrey et al, 2016; Ribeiro Coimbra & Noakes, 2021).…”
Section: Discussionsupporting
confidence: 82%
“…This has been described as a major public health concern (Glenn and Klonsky, 2013). There is evidence that adolescents from non-clinical populations are at high risk of self-harm (Monto et al, 2018), and that these risks increase further for CYP admitted to mental health inpatient settings (Kipoulas et al, 2021). A recent retrospective review of medical records for 105 children admitted to a mental health inpatient unit found that 66% had reported thoughts of self-harm, and 61% had engaged in self-harm behaviours (Kipoulas et al, 2021).…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews of the literature suggest a wide range from 1% to 21% of patients may self-injure while in inpatient care, influenced greatly by the clinical profile of patients within a setting (James et al, 2012). More recent research has identified rates of self-harm upward of 60% among young people during inpatient admissions (Kipoulas et al, 2021). While a high-risk population, inpatient settings allow for immediate support from nursing and other clinical staff to intervene and prevent incidents when possible.…”
Section: Intrapersonal Predictors Of Nssimentioning
confidence: 99%
“…Self-harm and suicidality are among one of the most common reasons for mental health inpatient admissions [8,13,67]. Children admitted to acute mental health services for self-harm and suicidal behaviours are believed to have greater mental health issues when compared to peers admitted for other reasons [68]. These adolescents also possess more risk factors heightening their vulnerability including low self-esteem, maltreatment and dysfunctional families [8].…”
Section: Suicide and Self-harmmentioning
confidence: 99%